Space-making effect for new bone formation by suppressing scar contraction of mucosal epithelium of rat tooth extraction wound using diode laser and CO2 laser treatment - Yusuke Taniguchi; Etsuko Matsuzaki; Yuki Daigo; Takashi Tsutsumi; Hiroshi Fukuoka; Kae Kakura; Kei Egashira; Kazuya Takahashi; Hirofumi Kido (Elsevier, 2022)
Background/purpose: As an extraction wound closes, the mucosal epithelium of the tooth extraction wound impedes the space for new bone formation by invading into the extraction socket. Thus, the height of the alveolar crest decreases, causing significant depression of the alveolar mucosa. In this study, we created a rat tooth extraction model and examined the effects of laser irradiation by CO2 and diode on the dynamics of myofibroblast expression through α-SMA, and TGF-β1. Materials and methods: After tooth extraction of five-week-old male Wistar rats, they were divided into two laser treatment groups (CO2 laser or diode laser was irradiated into tooth extraction socket) and non-laser treatment group (control group). Surrounding tissues, including the extraction socket, were removed at 3, 5, 7, and 21 days after tooth extraction and the expression of α-SMA and TGF-β1 was verified using immunohistological techniques (6 animals in each group and each period, 72 animals in total). Results: α-SMA-positive cells and TGF-β1-positive areas were significantly lower in the two laser treatment groups than in the control group. Particularly, the diode group almost had no TGF-β1-positive areas on the 21st day when healing after tooth extraction was deemed to be completed. Conclusion: Both CO2 and diode laser irradiation of tooth extraction wounds decreases α-SMA-positive cells and TGF-β1-positive areas. Further, it causes a decrease in myofibroblast expression and suppresses the invasion of mucosal epithelium into the extraction socket. Therefore, laser irradiation may exert a space-making effect for new bone formation and also contribute to socket preservation.